This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: → + = + 4x 6 x2 3x At this point, we need to move everything over with the x² by subtracting 4x and 6. → + 4x 6-- = +--4x 6 x2 3x 4x 6 Combine the 3x – 4x to get -1x =-- 0 x2 1x 6 Now factor this: = - ( + ) 0 x 3 x 2 Now solve for each- = + = : = = -x 3 0 or x 2 0 thus x 3 or x 2 At this point, you could check the answers if you wanted by plugging back into the original equation: + + = 1x 1x 3 12 first try it with x = 3 and then with x = -2. Both answers should check. If one answer gives a 0 in the denominator, we have to throw that answer out. In this example, both answers check....
View Full Document
This note was uploaded on 08/17/2011 for the course MAT117 MAT 117 taught by Professor Ranjitrebello during the Spring '09 term at University of Phoenix.
- Spring '09